1995
DOI: 10.1016/0014-5793(95)01225-4
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of mitochondrial mRNAs in the mdx mouse model for Duchenne muscular dystrophy

Abstract: In our search for genes up-or down-regulated genes in the mdx mouse model for Duchenne muscular dystrophy, we isolated a down-regulated mitochondrial DNA clone. In addition to this clone, all protein-coding mitochondrial genes tested had tissue-specific and age independent down-regulated expression. This implied mechanisms at the RNA level since no change in the mitochondrial DNA contents were detected. Cytocbrome c oxidase activity showed the same range of down-regulated expression. These data provide a molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 27 publications
4
10
0
Order By: Relevance
“…Downregulation of these genes, exclusively observed in mdx hindlimb muscles, indicated an impaired ATP synthesis and an alteration of metabolite supply for muscle activity. These findings served as a confirmation of observations by others that showed that the hindlimb (peripheral) muscles in DMD patients (2,11,49) and mdx mice (19,20,27) are affected by a generalized dysfunction of their energy machinery. The concomitant observation that the same gene set did not display differential expression in mdx diaphragm muscle indicated that the progressive and dramatic destruction of fibers from this muscle type possibly occurs without large perturbations of the metabolic machinery.…”
Section: Conclusion 2: Dystrophin Deficiency Causes Different Perturbsupporting
confidence: 88%
“…Downregulation of these genes, exclusively observed in mdx hindlimb muscles, indicated an impaired ATP synthesis and an alteration of metabolite supply for muscle activity. These findings served as a confirmation of observations by others that showed that the hindlimb (peripheral) muscles in DMD patients (2,11,49) and mdx mice (19,20,27) are affected by a generalized dysfunction of their energy machinery. The concomitant observation that the same gene set did not display differential expression in mdx diaphragm muscle indicated that the progressive and dramatic destruction of fibers from this muscle type possibly occurs without large perturbations of the metabolic machinery.…”
Section: Conclusion 2: Dystrophin Deficiency Causes Different Perturbsupporting
confidence: 88%
“…Muscle dystrophy and other muscle diseases are often associated with decline in nuclear-encoded mitochondrial gene expression or mitochondrial dysfunction (Chen et al, 2000;Gannoun-Zaki et al, 1995;Kuznetsov et al, 1998). To determine whether the primary effect of the Ewg null mutation is on muscle degeneration with consequent mitochondrial defects or the reverse causality of a primary mitochondrial defect leading to muscle degeneration, a knockdown of Opa1-like was performed.…”
Section: Results (Supplementary Materialsmentioning
confidence: 99%
“…The values Apt/Apo and Ant/Ano may be approximated as nearly constant values 1.57 and 1.38, respectively, independent of Apr or Anr (see Table 1) the progressive debilitating disorder of DMD. In addition, changes in gene expression in dystrophin-deficient skeletal muscles (Gannoun-Zaki et al 1995;Chen et al 2000;Tkatchenko et al 2001;Tseng et al 2002;Noguchi et al 2003;Nakayama et al 2004) are possibly due to oxidative DNA damage which would not be lethal lesions but mutagenic lesions. Our new technique for the assessment of oxidative stress in nuclear DNA in tissues would be applicable for the quantitative assay of other oxidative products of DNA bases (Wallace 2002;Bjelland and Seeberg 2003) if their specific antibodies are available.…”
Section: Discussionmentioning
confidence: 96%